A near-infrared squaraine dye for Cu2+-specific detection and fluorescence imaging in living cells and mice. (October 2022) - Yu, Lijia; Fan, Xinli; Zhao, Han; Ding, Chunguang; Zhang, Yinglin; Fan, Jingguang; Tang, Xinjing
Abstract: Herein, a highly selective and sensitive squaraine dye (F-0) for Cu 2+ detection was developed. Upon addition of Cu 2+, F-0 could greatly decrease absorption peak accompanying with fluorescent quenching about 170 folds. The detection limit can reach as low as 7.2 nmol/L. F-0 showed excellent water solubility and achieved naked eye detection of Cu 2+ . A paper strip pre-stained with F-0 solution was fabricated and showed color changed from blue to colorless upon addition of Cu 2+ . F-0 exhibited highly specific to Cu 2+ over other metal ions. Furthermore, on the basic of low cell cytotoxicity, F-0 could be utilized to monitor Cu 2+ in living cell and mice via fluorescence imaging. These results showed that F-0 has great potential for a more complex applications. Graphical abstract: Image 1